2017
DOI: 10.3842/sigma.2017.008
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Quantum Superintegrability of Stäckel Systems

Abstract: Abstract. In this paper we discuss maximal superintegrability of both classical and quantum Stäckel systems. We prove a sufficient condition for a flat or constant curvature Stäckel system to be maximally superintegrable. Further, we prove a sufficient condition for a Stäckel transform to preserve maximal superintegrability and we apply this condition to our class of Stäckel systems, which yields new maximally superintegrable systems as conformal deformations of the original systems. Further, we demonstrate ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In Section 4 we prove a theorem (Theorem 4.1) which establishes an explicit relation between Poisson algebras of h i and Lie-algebras of the corresponding non-homogeneous hydrodynamic vector fields (1.1). In Section 5 we exploit the notion of Stäckel transform [3,4,8,14,21] and analyze which of our systems h i can be mapped by this transform to new systemsh i in such a way that the Hamiltoniansh i also constitute an algebra. In this way we obtain new non-homogeneous hydrodynamic equations.…”
Section: Arxiv:170602873v2 [Nlinsi] 28 Sep 2017mentioning
confidence: 99%
See 2 more Smart Citations
“…In Section 4 we prove a theorem (Theorem 4.1) which establishes an explicit relation between Poisson algebras of h i and Lie-algebras of the corresponding non-homogeneous hydrodynamic vector fields (1.1). In Section 5 we exploit the notion of Stäckel transform [3,4,8,14,21] and analyze which of our systems h i can be mapped by this transform to new systemsh i in such a way that the Hamiltoniansh i also constitute an algebra. In this way we obtain new non-homogeneous hydrodynamic equations.…”
Section: Arxiv:170602873v2 [Nlinsi] 28 Sep 2017mentioning
confidence: 99%
“…Stäckel transform is a functional transform that maps a Liouville integrable system into a new integrable system, and in particular it maps a Stäckel system into a new Stäckel systems [3,8,14,21], which explains its name. In [4] the authors considered the action of Stäckel transform on superintegrable systems in such a way that it preserves superintegrability. It was found that only particular one-parameter Stäckel transforms preserve superintegrability.…”
Section: Stäckel Transform and New Non-homogeneous Hydrodynamic Killi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [5], an alternative quantization procedure of Stäckel systems is considered and applied in [6] to a class of superintegrable Stäckel systems with all quadratic in the momenta constants of motion. The procedure gives separable, and superintegrable, Schrödinger operators even when the Robertson condition is not verified.…”
Section: Modified Laplace-beltrami Quantizationsmentioning
confidence: 99%
“…In paper [6] we demonstrated how to generate the Hamiltonians Hi of the γ-class (1.1) as a multiparameter Stäckel transform [10,9,12,13,11,5,7] of Hamiltonians H i from the class (1.2). Also, in the recent paper [8] the authors found Lax pairs (L(λ), U i (λ)), i = 1, .…”
Section: Introductionmentioning
confidence: 99%